LINC01123 aggravates cerebral ischemia reperfusion injury by targeting miR-654-5p to upregulate METTL7A - Xiaoyang Feng; Jia Liu (Scientific Reports)
Abstract LINC01123 is up-regulated in acute cerebral infarction, but its role in cerebral ischemia/reperfusion injury (CIRI) is not fully understood. In vivo and in vitro models of CIRI were established using middle cerebral artery occlusion/reperfusion (MCAO/R) in rats and oxygen-glucose deprivation/reoxygenation (OGD/R) in SH-SY5Y cells. Key parameters, including cerebral infarct volume, brain water content, neurological deficits, apoptosis, and oxidative stress, were assessed. Results showed that LINC01123 was up-regulated in both MCAO/R rats and OGD/R-treated SH-SY5Y cells. Silencing LINC01123 reduced brain injury, apoptosis, and oxidative stress. Mechanistically, LINC01123 interacts with miR-654-5p, which targets methyltransferase like 7 A (METTL7A). OGD/R stimulation suppressed miR-654-5p and increased METTL7A levels. Inhibiting miR-654-5p or overexpressing METTL7A counteracted the protective effects of LINC01123 silencing from OGD/R-induced cell injury. In conclusion, these findings suggest that LINC01123 aggravates CIRI via the miR-654-5p/METTL7A axis, indicating its potential as a therapeutic target for CIRI.